Cytostatic Effects of Avocado Oil Using Single-cell Gel Electrophoresis (Comet Assay): An Evaluation - Uthirapathy, Subasini (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
The goal of this paper is to assess the mutagenicand genotoxic potentials of avocado oil made from the fruit pulp of Persea Americana, a member of the Lauraceae family.Michigan Cancer Foundation-7 (MCF-7) cells are used in the 3-4,5 dimethylthiazol-2yl-2,5-diphenyl tetrazolium bromide (MTT) test to examine the possible antiproliferative and cytostatic qualities of different doses of avocado oil, and MCF-7 cells are used in the comet assay to examine the potential cytostatic effects of avocado oil extracted from the avocado fruit. DNA in human breast cancer cells is partially damaged by avocado oil. However, DNA damage at low, medium, and high levels was discovered in the positive control. Without positive control, the DNA damage level falls in the low, middle, and high ranges. The MTT assay shows that avocado oil exerts a dose-dependent cytostatic impact on human breast cancer MCF-7 cells with an IC50 value of 379.2 μg/mL, which is the IC50 value that causes genotoxicity in the comet assay.